Career Development, Compensation, and Organizational Culture as Predictors of Employee Retention: The Mediating Role of Organizational Commitment in the Fire and Rescue Service of Bandar Lampung - Anggun Mona Maharani; Nur Aminah; Zenta Eliza; Febrianty Febrianty; Reza Rahardian Pratama (IJBLE Scientific Publications Community Inc., 2026)
Employee retention is strategically important in public safety organizations because operational continuity depends on employees who are technically competent, committed, and willing to remain in the organization. This study examines the effects of career development, compensation, and organizational culture on employee retention through organizational commitment at the Fire and Rescue Service of Bandar Lampung, Indonesia. The study used a quantitative explanatory design with 100 respondents selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The measurement model met the requirements for convergent validity, discriminant validity, and internal consistency reliability. The structural model shows that career development has a positive and significant effect on organizational commitment and employee retention. Compensation has no significant effect on organizational commitment but has a positive and significant effect on employee retention. Organizational culture has a positive and significant effect on organizational commitment but does not directly affect employee retention. Organizational commitment positively affects employee retention and mediates the effects of career development and organizational culture on employee retention; however, it does not mediate the effect of compensation. The R-square value for employee retention is 0.796, indicating that the model explains 79.6% of the variance in retention. These findings suggest that retention in a public safety agency can be strengthened through clearer career pathways, appropriate compensation, and organizational commitment built by a supportive organizational culture.